ANALYSIS OF FORMAL TEXT - Sulaymonov Samariddin; Abdurakhmanova Zilola (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: The analysis of formal text serves as a crucial tool for understanding and interpreting complex written materials. It involves a systematic examination of the language, structure, and content of formal texts, such as academic articles, legal documents, or business reports. By scrutinizing these texts, analysts can uncover underlying meanings, identify key arguments, and evaluate the effectiveness of the author's communication strategies.